Habits of Mind Affect on Mathematical Comprehension Ability - Rene Norman (Ridwan Institute, 2022)
This research was conducted in Sekolah Alam Indonesia Elementary School. The purpose of this study was to determine the effect of Habits Of Mind on mathematical ability. The research method used was a survey method. The number of samples that the researchers took was 40 students from a total population of 150 students, which were taken using the proportional random sampling technique. The instrument used is a written test instrument with 10 items. The result of this research is that there is a significant influence between habits of mind on mathematical understanding ability. This is evident from the calculation of the normality test, the mathematical understanding ability of the value of Lo < Ltable (0.1549 < 0.173) then H0 accepted. It is concluded that the mathematical understanding ability data come from a normally distributed population, as well as in classes taught with the ability mathematical understanding Lo < Ltable (0.1549 < 0.173) then H0 accepted. It is concluded that the data on the mathematical comprehension ability of the population is normally distributed.